PERANAN SERVICE QUALITY TERHADAP PATIENT REVISIT INTENTION MELALUI PATIENT SATISFACTION PADA RUMAH SAKIT UMUM DAN RUMAH SAKIT SWASTA TIPE B - Febry Adhiana (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2008)
Backg of nd: the increasing of awareness in health care by Indonesian people especially in Jakart Healthcare that health care professionals are highly dependent on each other to provide and coordi ate services of high value for human beings. Patients usually prefer to go to private hospitals hoping tc receive high service quality. But in fact, public hospitals have a good quality service also becau e ft is supported by the government.Object ve to compare service quality, patient satisfaction and patient revisit intention of public and privatE hospitals.Resea h design: this research applies to public and private hospitals in Jakarta and questionnaires were s read away to 97 respondents or patients from some public and private hospitals in Jakarta by usi g purpose sampling.Findin s: There are no differences between private and public hospitals in service quality, patient satisf Um and patient revisit intention. Finally the implications of the results are highlighted for health :are managers.